Impacts of government financial assistance on market structure, conduct and performance of food manufacturing SMEs in Malaysia - Abdul Aziz, Norhasmat (2019)
As Malaysia moves from being an agriculture-based economy to manufacturing-based economy, the contribution of the primary production tends to decline, and the processing of higher value food products increases. Small and medium enterprises (SMEs) played an essential role in food manufacturing industry and contribute towards input for gross domestic product (GDP) and jobs creation. Since 2012, the Malaysian government has allocated a substantial budget to speed up the development of SMEs and to make sure a further essential contribution to national growth. Nevertheless, the failure rate of SMEs is considerably high. Data indicated that even with the government’s assistances, the number of SMEs in food manufacturing industry that was forced to close down remain high. This research aims to evaluate the impact of government financial assistance towards market structure, conduct and performance of SMEs in the Malaysian food manufacturing industry which contributed 17.5% of the nation’s manufacturing output. Hence this research aims to contribute in the enhancement of government’s budget allocation and development of SMEs in the food manufacturing industry in Malaysia and achieve the objectives of SME Masterplan 2012-2020 in enhancing SMEs’ contribution to national GDP to 41 percent and exports to 23 percent by 2020. Conceptual framework of this study was based on structure, conduct and performance paradigm as it was found to be closely related to the variables to be studied. Complete data of 140 SMEs in the food manufacturing industry was obtained from SME Corporations and the Companies Commission of Malaysia for the years 2013-2017 and conducted empirical regression analysis based on 5,600 observations. Descriptive analysis, market structure, market conduct and market performance analysis, and panel regression analysis were used to analyze the data using Stata software. Overall, the value of concentration ratio 4 (CR4) and Herfindahl Hirschman Index (HHI) indicate a moderately concentrated and a competitive market level while the Gini Coefficient value reveals an unequal distribution of market share among the competing companies in the industry. The overall results of market conduct of the industry suggest that high capital intensity serves as an entry barrier for the industry as SMEs obtained high amount of debt to operate their businesses and investors need to invest on assets in order to compete in the food manufacturing industry. The profitability ratios indicate stable returns over the study period, but a lower profitability as compared to other industry in Malaysia. Financial incentive is found to have positive significant effect on the conduct and performance of SMEs and tax incentive have positive significant effect in influencing market structure and market conduct while having no significant effect on the performance of SMEs. Based on this study, it is recommended that the government should choose appropriate financial assistance that can reduce debt of SMEs especially in acquiring assets. Formulating better financial incentive that can increase the SMEs expenditure in promoting their product will increase their competitiveness in the market. A better policy in awarding more tax incentive to SMEs will affect the structure of the market. This study has contributed to SCP paradigm as it demonstrated the impacts of government financial assistance in the form of financial and tax incentive towards the market structure, conduct and performance of SMEs in the Malaysian food manufacturing industry. Future researches are advised to include other types of government assistances to wholly assess the impact towards market structure, conduct and performance of SMEs and to include higher number of samples.